2015
DOI: 10.4137/bbi.s30522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pseudorabies Virus Infection on the Tracheobronchial Lymph Node Transcriptome

Abstract: This study represents the first swine transcriptome hive plots created from gene set enrichment analysis (GSEA) data and provides a novel insight into the global transcriptome changes occurring in tracheobronchial lymph nodes (TBLN) and spanning the swine genome. RNA isolated from draining TBLN from 5-week-old pigs, either clinically infected with a feral isolate of Pseudorabies virus or uninfected, was interrogated using Illumina Digital Gene Expression Tag Profiling. More than 100 million tag sequences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The use of the network lead to add 9 terms strictly related to the immune system and correctly highlighting the immunogenic effect of the virus ( Supplementary Table S5). Thus, NETGE-PLUS directly pointed out the activation of immunological processes involved in the response to virus, and like Miller et al [14] gene sets related to the cytokines and other molecular mediators of immune response were here evidenced. Supplementary Table S5.…”
Section: Effect Of the Pseudorabies Virus Infection On The Swine Transupporting
confidence: 70%
See 1 more Smart Citation
“…The use of the network lead to add 9 terms strictly related to the immune system and correctly highlighting the immunogenic effect of the virus ( Supplementary Table S5). Thus, NETGE-PLUS directly pointed out the activation of immunological processes involved in the response to virus, and like Miller et al [14] gene sets related to the cytokines and other molecular mediators of immune response were here evidenced. Supplementary Table S5.…”
Section: Effect Of the Pseudorabies Virus Infection On The Swine Transupporting
confidence: 70%
“…To characterize the host-virus interactions, Miller et al [14] investigated By using GSEA, Miller et al [14] observed the induction of the host innate immune response, including the upregulation of interferon responsive genes, inflammatory response genes, and cytokine-cytokine receptor interaction.…”
Section: Effect Of the Pseudorabies Virus Infection On The Swine Tranmentioning
confidence: 99%
“…The experimental design used in the original study is described in full in Miller et al, 2015 [1] and consisted of RNA isolation from porcine tracheobronchial lymph node (TBLN) tissue from infected and non-infected pigs. Pathogen-free pigs, between 4 and 5 weeks of age ( N = 40) were split into two equal ( n = 20) treatment groups and received intranasal inoculations of either a sham inoculum or a 1 × 10 6 cell culture infectious dose (CCID 50 ) of Pseudorabies virus Florida strain isolate 268 (FS 268).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The leading edge analysis allows for the GSEA to determine which subsets (referred to as the leading edge subset) of genes contributed the most to the enrichment signal of a given gene set's leading edge or core enrichment [3] . The leading edge analysis is determined from the enrichment score (ES), which is defined as the maximum deviation from zero [1] , [3] . The analysis is accomplished by setting the GSEA software parameters to define subsets of the core genes that drive the enrichment score of the GSEA clusters.…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…The lymph node is the place where the innate (early, non-specific) immune response talks to the adaptive (later, specific) immune system with the TBLN working specifically to drain lymphatic fluids from virus-infected lung tissues. While the TBLN contains a number of cell types, the advantage of sampling the TBLN is that both directly effect the virus on cells in the lymph nodes, as well as indirect effects on lymph nodes draining the lungs can be examined, giving our study an indication of the real host response [12,13]. While PRRSV, PCV-2, and IAV-S can induce respiratory disease in pigs that may appear somewhat clinically similar, [13][14][15][16], the cellular specificities, kinetics of clinical disease onset and duration of infection are different for each virus.…”
Section: Introductionmentioning
confidence: 99%